Caudal epidural steroid injection versus transforaminal ESI for unilateral S1 radiculopathy: a prospective, randomized trial - (:unkn) unknown (My University, 2023)
OBJECTIVE: Epidural steroid injections are frequently performed to manage radicular symptoms. Most research investigating the effectiveness of different routes of epidural injections were conducted with non-homogeneous groups. In this study our aim was to investigate the efficacy of caudal versus transforaminal approaches in patients with unilateral S1 radiculopathy secondary to a paracentral L5-S1 disc herniation. STUDY DESIGN: Prospective, randomized clinical trial. SETTING: A university hospital pain management center. METHODS: The study was conducted between January 2022 and February 2023. Patients with unilateral S1 radiculopathy were randomly divided into two groups: the caudal epidural steroid injection (CESI) and the transforaminal epidural steroid injection (TFESI) group. Severity of pain and disability were assessed with Numeric Rating Scale (NRS-11) and Oswestry Disability Index (ODI) at baseline, 3 weeks, and 3 months after treatment. Fifty percent or more improvement in NRS-11 was defined as treatment success. Fluoroscopy time and doses of exposed radiation were also recorded. RESULTS: A total of 60 patients were included in the final analysis (n = 30 for each group). Significant improvement in pain and disability scores was observed at 3rd week and 3rd month compared to baseline (P < .001). Treatment success rate at 3rd month was 77% for the CESI group and 73% for the TFESI group without any significant difference between the groups (P = .766). CONCLUSIONS: CESI is equally effective as TFESI in the management of S1 radiculopathy due to a paracentral L5-S1 disc herniation. Both approaches can reduce pain and disability, while CESI requires shorter fluoroscopy time and less radiation exposure.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; caudal epidural steroid injection; disc herniation; lumbosacral radiculopathy; transforaminal epidural steroid injection